2013
DOI: 10.2106/jbjs.k.01549
|View full text |Cite
|
Sign up to set email alerts
|

Complications Following Tension-Band Fixation of Patellar Fractures with Cannulated Screws Compared with Kirschner Wires

Abstract: Serious complications are uncommon following treatment of patellar fractures with a modified tension-band technique, with use of either Kirschner wires or cannulated screws. In both groups the rate of fixation failure was low, as was the rate of postoperative infection. Symptomatic implants, the most common complication observed, were twice as frequent in patients treated with Kirschner wires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
167
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(175 citation statements)
references
References 19 publications
5
167
1
2
Order By: Relevance
“…6 However, this technique led to k-wire related complications post-operatively like backing out of wires, pain and irritation due to k-wires. 8 These complications left the surgeon in dilemma of removing the implant and risking non-union or leaving it inside with the concomitant patient suffering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, this technique led to k-wire related complications post-operatively like backing out of wires, pain and irritation due to k-wires. 8 These complications left the surgeon in dilemma of removing the implant and risking non-union or leaving it inside with the concomitant patient suffering.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of implant removal for symptomatic hardware have ranged from 0% to 50%. 8 Although symptomatic implant irritation is not as serious a complication as fixation failure or postoperative infection, it does require the patient to undergo a second operation, which carries inherent surgical risk and increases the overall cost of fracture care. 9 Thus a method needs to be devised by which the re-operation rates can be decreased without compromising the union rates.…”
Section: ( F I G _ 4 ) T D $ F I G ]mentioning
confidence: 99%
“…Bursitis around the Stainless steel wire knots and migrated K wires are very common in these patients. Hoshino et al in their study demonstrated an implant removal rate of 37% and 23% for patella fracture treated respectively with K-wires and cannulated screws and LeBrun et al reported a hardware removal rate of approximately 52% at a mean of 6.5 years of follow-up [9,13] . On the basis of these results, some authors have advocated the use of nonmetallic implants, such as non absorbable sutures and biodegradable cannulated screws [6-10, 18, 22] .…”
Section: Discussionmentioning
confidence: 96%
“…Hardware removal is a very common requirement for these reasons in patella fracture treatment. Non absorbable braided sutures are been used by many authors in various ways to avoid these hardware problems [6][7][8][9][10][11]18] . Internal fixation of patella with vertical wiring augmented with Krackow sutures are also being done for inferior pole patella fractures [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Excessive bleeding, increased operative time, and the risk of prolonged anaesthesia time the patient is under. 7,10,15,17,18 Postoperative complications with this method, are mostly implant-related. Other major issues include wire breakage and migration of the wire away from the site leading to implant failure, seen after operative procedure limitations are loss of reduction and implant irritation, with increased rates of subsequent implant removal for symptomatic hardware.…”
Section: Introductionmentioning
confidence: 99%